Electrical stress probing recovery efficiency of 28 nm HK/MG nMOSFETs using decoupled plasma nitridation treatment. (July 2018) - Wang, Shea-Jue; Sung, Shun-Ping; Wang, Mu-Chun; Huang, Heng-Sheng; Chen, Shuang-Yuan; Fan, Shou-Kong
Abstract: Exposing the feasible nitrogen concentration and annealing temperatures with decoupled plasma nitridation (DPN) treatment to the high-k dielectric after deposition as gate dielectric is impressive to raise the high-k value and against the gate leakage. The study not only focuses on the quality of high-k dielectric, but the reliability concern. Using the voltage stress sensing and analyzing the recovery of gate dielectric, comparing with different nitrogen concentration and different annealing temperatures is done. The consequences show the tested device with higher annealing temperature has the better performance rather than the lower one in recovery and drive current, but the worse in reliability stress, especially in threshold voltage (VT ) shift. If the tested devices were under the same nitridation treatment, the performance and recovery efficiency of the tested device with the lower nitrogen concentration are better than those of the higher one, but the degradation rate is more distinct. Highlights: The cross-sectional profile of a HK/MG MOSFET is clearly presented. The influence of temperature annealing to drive current after high-k gate dielectric deposition is illustrated. The impact of nitrogen concentration treatment to drive current after high-k gate dielectric deposition is demonstrated. The recovering effect after stress for the annealing devices was investigated. The recovering effect after stress for the N2 concentration treatment was compared and related to the device reliability concern.